KARAKTERISTIK SEGITIGA LUCAS - Nurshiami, Siti Rahmah; Wardayani, Ari; Setiani, Kana Hasmi (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
Lucas triangle is an array of coeficients of a polynomial forming a pattern which is similar to Pascal triangle. This research studies Lucas triangle and its properties. The research results show that every row in Lucas triangle is begun by the number 1 and is ended by the number 2,  the sum of the first n terms of number of 1th column is equal to the number at th row, 2nd column. Besides, the number at nth row and  th column of Lucas triangle is  for , the sum of the first n terms of number of jth column is equal to the number at th row,  column for . The number of Lucas triangle is the sum of two number terms in preceded row, that is the number at  th row,  and the number at th row, . Then, the sum of coefficients of each  row of Lucas triangle is .